Effect of Problem-Based Learning Model on Critical Thinking Skills in Civic Education Learning - Sari, Noor Asni; Dasna, I Wayan; Kusumaningrum, Shirly Rizki; Sitanggang, Indah (Indonesia Approach Education, 2024)
Research has been conducted on the problem by discussing the effect of the Problem Base Learning model to improve students' critical thinking skills in civic education subjects in class III elementtary school Srewendari. The study aims to determine the effect of the Problem-Based Learning model on critical thinking skills in analyzing facts, presenting arguments, providing conclusions, conveying the concept of Pancasila, arguing, independent thinking in reflection, solving problems and recognizing information found in class III elementtary school in Srewendari Malang City. This research is quasi-experimental (quasi experiment) using the Nonequivalent groups pretest-posttest control group design refers to this design, the effect of the PBL model on critical thinking skills will be known through the comparison of the average posttest score of critical thinking skills between the experimental class and the control group through the t-test. The population of this study was third-grade students of public elementary schools in Malang City. The research conducted has samples taken in the form of experimental class a as many as three and control class b as many as three, data collected through observation with rating scale instruments and tests with instruments in the form of test or evaluation questions conducted in class. The data were analyzed quantitatively through a difference test with a confidence interval greater than 95%. The results of the research conducted show that the application of the Problem-Based Learning model has a positive and significant effect on student's critical thinking skills in civic education subjects.